Fiber optic sensor for hydrostatic pressure and temperature measurement in riverbanks monitoring. (August 2016) - Schenato, Luca; Aneesh, Rajendran; Palmieri, Luca; Galtarossa, Andrea; Pasuto, Alessandro
Abstract: An optical fiber sensor for the simultaneous measurement of hydrostatic pressure and temperature in soil embankments is presented. It exploits the differential strain induced on a fiber in a dual–chamber case, constituting the sensor body. The strain, either induced by the pressure or by the temperature, is optically measured by means of coherent frequency domain reflectometry and variations induced by the two physical phenomena are discriminated because of the different behavior of the two chambers. Characterization of the sensor is presented and discussed. The prototype shows promising performance: temperature and pressure sensitivities are approximately −7 GHz/°C and −3.2 GHz/kPa, respectively, with accuracies of 0.5 °C and 0.3 kPa. Abstract : Highlights: An optical fiber sensor for hydrostatic pressure and temperature in soil embankments is developed. The sensor exploits the differential strain affecting a fiber in a dual–chamber case. Coherent optical frequency domain reflectometry is used to measure the strain.